IN SILICO INTERACTION ANALYSIS OF SELECTED 5 TROPANE ALKALOIDS AGAINST ORAL CANCER DRUG TARGETS - Faiz, Nadhirah; T, Lakshmi; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
The aim is to study the interaction of Indole alkaloids against 2 oral carcinoma drug targets by in silico docking using iGemdock tool.In this generation, technology has become so advanced that we are able to now achieve what was believed 20 years ago to be impossible. One such advancement is in silico interactions. It is a virtual screening which enables us to bind two compounds and check the affinity of the binding. This helps us to first screen the activity of the two compounds before money, time and energy is spent in manually performing the activity and then arriving at a failure. We will be able to concentrate on the compounds which show us positive results in the in silico interactions, thus helping us in conserving time, expenditure and energy.Ajmalicine shows good interaction with both drug targets and possesses the best fitness energy of all 5 tropane alkaloids.